ANALISIS PENGARUH KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP LOYALITAS PELANGGAN DENGAN KEPUASAN PELANGGAN SEBAGAI VARIABEL INTERVENING - Findila Ariyanis, Untung Sriwidodo & Edi Wibowo (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2017)
This study aims to analyze the significance effect of product quality and servicequality to customer satisfaction, analyze the significance of product quality, servicequality and customer satisfaction to customer loyalty and analyze the significance ofeffect of product quality and service quality on customer loyalty with customersatisfaction as intervening variable. This study is a survey of restaurant customers KFCHartono Mall in Solo Baru. Samples of 100 people with purposive sampling technique.Data collection techniques used questionnaires. Data analysis technique used pathanalysis. The results showed that product quality and service quality has positive andsignificant effect on customer satisfaction. Product quality, service quality and customersatisfaction have a positive and significant effect on customer loyalty. Product qualityand service quality has positive and significant effect on customer loyalty with customersatisfaction as intervening variable.Keywords: product quality, service quality, satisfaction, loyalty